Orality and written in the Pentecostal Theology: successes, risks and possibilities - Pommerening, Claiton Ivan (2011)
The Evangelical Church Assembly of God teaches its congregation especially through orality. This paper shows the main characteristics of oral cultures, the power and dynamic of language and sound, how this cultures use orality in order to spread their wisdom and how the interface between oral culture and written culture happens. It also explains the main characteristics of orality in the Assembly of God and its forms of expression through poimen, testimonies, preaching, glossolaia, Christian Harp and the mixture of oral and written culture in the use of Bible and lessons of the Sunday school as well as how these characteristics work together and separately in poor and elitized communities. At the end, this paper proposes how a Pentecostal theology should be; that is, that preserves orality and allows a formal theological thought.